Advancing quantitative clinical pharmacology competencies in Francophone Africa through an on-line learning framework - Nour Chtiba; Sihem Ait-Oudhia; Sonia Khier; Anna Chan Kwong; Innocent G. Asiimwe; Florence Gattacceca; Miriam Razgallah Khrouf; Paul Baverel; Celine Sarr; Anaïs Glatard; Julie Bertrand; Nada Abla; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Solute Transport in Bentonite Buffer Under Thermal Hydraulic Mechanical Coupling - Uy D. Vo; Mamadou Fall; Julio Á. I. Sedano; Maïwenn Humbezi-Desfeux; Jean-Michel Matray; Manuel Marcoux; Son T. Nguyen (Geotechnical and Geological Engineering, 2026)
This paper investigates solute transport processes in the bentonite buffer of a Deep Geological Repository (DGR) for used nuclear fuel, using the Canadian concept as an example. The design relies on a multi-barrier system in which the used fuel container (UFC) provides containment and the surrounding bentonite buffer protects the UFC while retarding radionuclide migration following a potential breach. Solute transport in the buffer is strongly influenced by coupled thermal-hydraulic-mechanical (THM) processes. A coupled THM-transport model was developed to evaluate (1) reactive transport of bisulfide $$\left({\text{H}\text{S}}^{-}\right)$$ HS - from the host rock to the UFC and associated UFC corrosion; and (2) radionuclide migration following a hypothetical UFC breach. The model builds on previous verification and validation and is further assessed against laboratory-scale bisulfide transport experiments and a large-scale thermal diffusion experiment at the Tournemire Underground Research Laboratory (France). The results show that temperature-dependent diffusion is the dominant transport mechanism, significantly enhancing solute migration, whereas hydraulic desaturation has limited influence and the Soret effect is negligible at repository scale. Under the reference conditions, adsorption and $$\text{F}\text{e}\text{S}$$ FeS precipitation delay detectable HS − flux to the UFC until approximately 5 × 10 5 years and limit the predicted corrosion depth to ~ 0.05 mm after one million years. In the breach scenario, the buffer effectively delays and attenuates moderately/strongly sorbing radionuclides (e.g., 135 Cs, 237 Np). The effectiveness in retarding radionuclides' migration is most sensitive to bentonite diffusivity and sorption capacity.

Pesticide Contamination in Freshwater Resources Across Senegal: Implications for Drinking Water Safety and Sustainable Aquaculture Development - Safietou Mbaye; Gaspard Conseil; Jean Fall; Dani Khoury; Marion Huguet-Cizo; Christophe Rosin; Frédéric Pierlot; Damien Banas (Water, Air, & Soil Pollution, 2026)

Infectious Diseases Management in Small‐Scale Freshwater Aquaculture in West Africa: Lessons for Low‐ and Middle‐Income Countries - Mame Boucar Diouf; Robane Faye; Ahou Rachel Koumi; Nounagnon Darius Tossavi; Enoutchy Fabrice Bouah; Ephigénie Ndew Dione; El Hadji Malick Sy Camara; Kadjo Henri Joel Niamien; Ué Clavier Zéa Bi; Atto Delphin Kouadio; El Hadji Papa Abdourahim Sy; Thérèse Adeline Fatou Gomis; et al. (Reviews in Aquaculture, 2026)
Infectious diseases are an increasing threat to food security, small‐scale livelihoods and the sustainability of aquaculture in low‐ and middle‐income countries (LMICs). In sub‐Saharan Africa, aquaculture is expanding rapidly but production systems often remain fragile. In West Africa, particularly in Benin, Côte d'Ivoire and Senegal, production remains modest despite rising demand. Interactions between farming practices, environmental exposures (e.g., contaminants and agricultural effluents) and pathogen emergence are poorly documented. Here we review evidence on production systems, reported pathogens, diagnostic and surveillance capacity in these three countries. We find that (i) production relies mainly on small‐scale ponds, cages often within integrated agro‐aquaculture systems with recurring constraints in biosecurity, water management and governance; (ii) available evidence is fragmented and uneven across pathogen groups, with most reports focusing on bacterial and parasitic conditions and major gaps for viruses, fungi, co‐infections, antimicrobial resistance and combined environmental pressures; and (iii) health management and laboratory capacities remain constrained, but existing networks and experience from terrestrial animal health provide entry points for integrated and participatory surveillance. We discuss these patterns through an exposome‐informed One Health lens, highlighting how multiple exposure pathways link farms, watersheds and nearby communities. Based on this synthesis, we outline research and policy priorities to strengthen health resilience and to support more sustainable small‐scale freshwater aquaculture in West Africa and, with relevance to other tropical LMIC settings.

Evaluating the impact of different agropastoral practices on wind erosion in western Sahel - Paul-Alain Raynal; Jean-Louis Rajot; Beatrice Marticorena; Abdourahmane Tall; Baptiste Lemaire; Jean-Alain Civil; Diouma Cor Fall; Gualbert Seraphin Dorego; Ibrahima Sarr; Issa Faye; Ambre Emmendoerffer; Henri Guillaume; et al. (CATENA, 2025)

Mississippi Valley-type mineralization in the Jurassic Smackover Formation, Gulf Coast Basin, USA: Controls on the origin of Zn-Pb-Ag systems in deep sedimentary basins - J. Richard Kyle; András Fall; Jean-Philippe Nicot (Journal of Geochemical Exploration, 2025)

Trace of change: How stigmergy maps social learning loops in Companion Modeling through participatory simulation - François Vendel; Oleksandr Zaitsev; Pierre Bommel; Ibra Touré; Jean-Daniel Cesaro; Penda Diop; Marieme Fall Ba; Tamsir Mbaye; Etienne Delay (Journal of Environmental Management, 2025)

Numerical simulation of solute transport in argillaceous rock under thermal gradient with a coupled THM-solute transport model - Uy Vo; Mamadou Fall; Julio Ángel Infante Sedano; Maïwenn Humbezi-Desfeux; Jean-Michel Matray; Manuel Marcoux; Thanh Son Nguyen (Geomechanics for Energy and the Environment, 2025)

Assessing the Effects of Guiera senegalensis, Pluchea odorata, and Piliostigma reticulatum Leaf Powder Supplementation on Growth, Immune Response, Digestive Histology, and Survival of Nile Tilapia (Oreochromis niloticus Linnaeus, 1758) Juveniles before and after Aeromonas hydrophila Infection - Paul M. Ndour; Jean Fall; Maria J. Darias; Domenico Caruso; Marc Canonne; Elodie Pepey; Sophie Hermet; Sokhna K. L. Fall; Malick Diouf; Samira Sarter (Fishes, 2024)
The effects of three medicinal plants in the feeds of juvenile Nile tilapia (Oreochromis niloticus) were investigated on growth, survival, immunity, and digestive histology at various inclusion levels: (A) Guiera senegalensis at 0, 1, 2, 4, and 8%; (B) Pluchea odorata at 0, 0.5, 1, 2, and 4%; (C) Piliostigma reticulatum at 0, 1, and 2%; and (D) a mixture of the three at 0, 1, and 2%. After 28 days of feeding, fish were infected with Aeromonas hydrophila for 12 days. The results showed that, except for G. senegalensis, the inclusion of the medicinal plants, alone or combined, enhanced the immune response. The diet with 4% P. odorata significantly increased plasma lysozyme and bactericidal activities without affecting feed conversion efficiency or growth. Despite improved immunity, none of the treatments enhanced post-infection survival rates. However, fish fed the 1% mixture showed healthier livers and intestines, with reduced cell swelling and normal lipid deposits, followed by the 2% mixture and the control. These results highlight the potential benefits of incorporating P. odorata and the plant mixture into the diets of Nile tilapia juveniles for enhancing their immune response against A. hydrophila.

Prospects and challenges of environmental DNA (eDNA) metabarcoding in mangrove restoration in Southeast Asia - Alison K. S. Wee; Severino G. Salmo III; Kannan Sivakumar; Amy Y-H Then; Mohammad Basyuni; Jean Fall; Kazi Ahsan Habib; Yukinobu Isowa; Venus Leopardas; Nasreen Peer; Maria D. Artigas-Ramirez; Kithsiri Ranawana; et al. (Frontiers in Marine Science, 2023)
Species detection using environmental DNA (eDNA) is a biomonitoring tool that can be widely applied to mangrove restoration and management. Compared to traditional surveys that are taxa-specific and time-consuming, eDNA metabarcoding offers a rapid, non-invasive and cost-efficient method for monitoring mangrove biodiversity and characterising the spatio-temporal distribution of multiple taxa simultaneously. General guidelines for eDNA metabarcoding are well-established for aquatic systems, but habitat-specific guidelines are still lacking. Mangrove habitats, as priority ecosystems for restoration in Southeast Asia, present unique prospects and challenges in these regards. Environmental DNA metabarcoding can be used to (1) track functional recovery in ecological restoration, (2) prioritise conservation areas, (3) provide early warning for threats, (4) monitor threatened taxa, (5) monitor response to climate change, and (6) support community-based restoration. However, these potential applications have yet been realized in Southeast Asia due to (1) technical challenges, (2) lack of standardised methods, (3) spatio-temporal difficulties in defining community, (4) data limitations, and (5) lack of funding, infrastructure and technical capacity. Successful implementation of eDNA metabarcoding in mangrove restoration activities would encourage the development of data-driven coastal management and equitable conservation programs. Eventually, this would promote Southeast Asia’s shared regional interests in food security, coastal defence and biodiversity conservation.

Sanitary quality improvement of fish produced in the northern Benin cotton basin water reservoirs by cage culture and fish transfer in agricultural contaminant-free water: human health implications - Rodrigue O. E. Pèlèbè; Ibrahim Imorou Toko; Issa N. Ouattara; Ulbad P. Tougan; Eloi Y. Attakpa; Jean Fall; Elie Montchowui (Tropical Animal Health and Production, 2020)

Listeria monocytogenes detected in vaginal self-samples of 2 women after spontaneous miscarriage, Senegal, West Africa - Ndeye Safietou Fall; Mariema Sarr; Nafissatou Diagne; Hubert Bassène; Cheikh Sokhna; Jean-Christophe Lagier; Didier Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Usefulness of MALDI-TOF Mass Spectrometry for Routine Identification of Candida Species in a Resource-Poor Setting - Doudou Sow; Bécaye Fall; Magatte Ndiaye; Bissoume Sambe Ba; Khadime Sylla; Roger Tine; Aminata Collé Lô; Annie Abiola; Boubacar Wade; Thérèse Dieng; Yémou Dieng; Jean Louis Ndiaye; et al. (Mycopathologia, 2015)

Quantitative loop-mediated isothermal amplification method for the detection of Vibrio nigripulchritudo in shrimp - Jean Fall; Gunimala Chakraborty; Tomoya Kono; Minoru Maeda; Yoshihiro Suzuki; Toshiaki Itami; Masahiro Sakai (Fisheries Science, 2011)

Variation in the distribution of monosaccharides in soil fractions in the mounds of termites with different feeding habits (Senegal) - Saïdou Sall; Alain Brauman; Saliou Fall; Corinne Rouland; Edouard Miambi; Jean-Luc Chotte (Biology and Fertility of Soils, 2002)